United States Delegation to the Fourth Special Session on its position on the Situation in Hungary - Héderváry, Claire de (1963)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United States. Mission to the United Nations The United States takes the view that pending further classification of the precise situation in Hungary, it would reserve its position regarding the credentials of the Hungarian delegation. It was noted that a number of steps had taken which appeared to have improved the situation of the Hungarian people. The United States delegation noted with satisfaction that the Secretary General would be also visiting Hungary in July 1963.